Methods for Prevention of Sexual Abuse among Adolescents: A Systematic Review - Tahereh MOKHTARIAN GILANI; Masoumeh SIMBAR; Nourossadat KARIMAN; Tayebeh MOKHTARIAN GILANI; Shahin BAZZAZIAN; Malihe GHIASVAND; Maryam HAJIESMAELLO; Samiyeh KAZEMI (Tehran University of Medical Sciences, 2020)
Background: One of the serious health concerns is rape to adolescents. It is caused by unwanted behaviors through threats, force and physical pressure. The purpose of this study was to review rape in adolescents and methods for its prevention. Methods: This systematic review study was conducted from 2000 to 2017 in the databases of PubMed, Google Scholar, Web of Science, and Scopus. The CONSORT was used to assess interventional studies. The evaluation of observational studies was performed using the STROBE tool by two researchers independently. Inclusion criteria were studies published from 2000 to 2017, in English languages, and on the samples of 10-20 yr old. Overall, 202 articles published from 2000 to 2017 in English languages were retrieved.  Of them, 154 articles were excluded due to lack of inclusion criteria and 38 articles were deleted due to lack of quality And non-relevance. Finally, 10 articles were selected. Results: In the review of interventional studies, the prevalence of sexual harassment and sexual assault by the means of adolescents' empowerment and education of self-defense techniques was significantly lower in the intervention group than the control group. In other non-interventional studies, there was a statistically significant relationship between the high level of knowledge and attitude of adolescents and the reduction of risk factors and sexual assault. Conclusion: Promotion of awareness and attitudes through evidence-based interventions can prevent sexual abuse in adolescents. Appropriate education programs in schools and adolescent centers to adolescent students and their caregivers can promote healthy relationships and prevent sexual harassment.